Caderno de leitura literária : A mulher que matou os peixes - Barreto Júnior, José Aldo (2020)
This essay aims to produce a literary reading notebook of the tale “The Woman Who Killed the Fishes” by Clarice Lispector, published in 1968, which aims to develop literary reading skills through the critical sense of students about the relation between man and pets, based on the debate proposed by the crisis of guilt of the narrator who apologizes for killing the little fishes from her aquarium. This play of persuasion her innocence results in seduction of the reader through the narrative of several cases in which the narrator helped several pets. In order to build a pedagogical practice of reflection on the importance of literary reading, teaching activities were developed for the literary reader of the sixth grade of elementary school. Pedagogically, it is proposed reading activities of other texts on the literary work of the relation between man and animals, emphasizing the intertextuality between them, in addition to the use of technologies as a tool for a further approximation between the literary text and the daily life of students. The product was built from five workshops offered in the second semester of 2019 to a state school in Sergipe. Methodologically, we explored the pleasure of literary reading through playful activities and with students 'participation in the use of digital technologies to disseminate the results of their interpretations, demonstrating how the union of such elements can make literary reading closer to students' reality. In this regard, it was produced as a learning object a reading notebook focused on the practice of the literary reading. The theoretical foundation of this notebook is supported for the following approaches: “aesthetic reader” by Umberto Eco (2004) who, in his essay “Model Reader” points out the importance of the reader to identify the incompleteness of the text, presupposing the reader's collaboration, “subjective reading”. Anne Rouxel (2013), who recognizes the reader's memory as one of the plausible reading strategies in playful pedagogical practices; and the 'reading cultural model' by Carlos Gomes (2011), which prioritizes the critical social formation of the reader linked to the appreciation the caution to be taken with the animals. According to these central concepts, we favor a literary reading model in which students can recognize the role of previous knowledge for effective reading comprehension, as well as the clues that allow the dialogue between these texts and their resulting meanings. Therefore, this reading notebook aims to develop reading skills through the critical sense of students about the relation between man and pet.